Modelos de reação-difusão com atividade catalítica - Mattos, Thiago Gomes de (2010)
Reaction-diffusion models have received much attention in the last decades due to its great potential for applications in various fields of Physics, Chemistry and Chemical Engineering, as well as in industrial processes. These models aim at a conection between the micro and macroscopic levels and incorporate mechanisms such as diffusion, reaction, desorption and adsorption, providing information on the efficiency of a process (e.g. conversion rates), and may help to understand experimental results. First, this thesis will discuss some of these models, such as the ZGB model for the oxidation of carbon monoxide, CO. Subsequently we will focus on our own work, showing how simple reaction-diffusion models with catalytic may yield results such as non-trivial dependence of conversion rate on temperature and geometry of a supported catalyst, and the existence of non-equilibrium phase transitions in a model with catalyst deactivation by poisoning.